2017
DOI: 10.1108/bfj-05-2016-0208
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the geography of Brazilian diet diversity

Abstract: Purpose The purpose of this paper is to present the evolution of Brazilian food patterns, based on the 2002-2003 and 2008-2009 Brazilian Household Budget Surveys (POFs), and to evaluate similarities in food acquisition among the Brazilian states, in search for the main drivers of the changes. Design/methodology/approach Using the data gathered from the 17 food groups within the POFs and multidimensional scaling, the Brazilian states were divided into groups and analysed according to their similarities in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…We understand that there is an association between geographic regions and nutritional misalignment. Our findings confirm the moderate spatial autocorrelation for Brazilian overweight that show that there is a higher prevalence of (9). IBGE Food Groups: 1-cereals and pulses; 2-starch flour and pasta; 3-coconuts, nuts, and walnuts; 4-vegetables; 5-fruits; 6-sugars and confectionery; 7-salts and condiments; 8-meat and offal; 9-fish; 10-canned and preserves; 11-birds and eggs; 12-dairy products; 13-bakery products; 14-processed meat; 15-beverages and infusions; 16-oils and fats; 17-prepared foods.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We understand that there is an association between geographic regions and nutritional misalignment. Our findings confirm the moderate spatial autocorrelation for Brazilian overweight that show that there is a higher prevalence of (9). IBGE Food Groups: 1-cereals and pulses; 2-starch flour and pasta; 3-coconuts, nuts, and walnuts; 4-vegetables; 5-fruits; 6-sugars and confectionery; 7-salts and condiments; 8-meat and offal; 9-fish; 10-canned and preserves; 11-birds and eggs; 12-dairy products; 13-bakery products; 14-processed meat; 15-beverages and infusions; 16-oils and fats; 17-prepared foods.…”
Section: Discussionsupporting
confidence: 89%
“…To standardize, all items were converted to the metric unit kilogram (kg). Concerning food types, the data were classified into the 17 groups pre-established by IBGE (2010): (1) cereals and legumes, (2) flour and pasta, (3) coconuts, chestnuts, and nuts, (4) vegetables, (5) fruits, (6) sugars and products of confectionery, (7) salts and condiments, (8) meats and offal, (9) fish, (10) canned and preserves, (11) poultry and eggs, (12) dairy products, (13) bakery, (14) industrialized meats, (15) beverages and infusions, (16) oils and fats, and (17) prepared foods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the same dynamics, Brazil is composed of different socio-economic contexts, which transforms food habits or food patterns and their consumer markets. Mores et al (2017), who studied the recent evolution of the Brazilian food standard, suggested that the main drivers of changes in the food patterns in different regions are associated with changes in the regional agricultural base, the availability of new foods and new cultures, and the change in the income of the population, which caused new dietary habits. These factors lead to a new FSC, which results in a greater supply of food and, consequently, to distinct behaviors of FLW in different Brazilian regions.…”
Section: Food Loss and Waste Along The Food Supply Chain In Brazilmentioning
confidence: 99%
“…A partir da similaridade da aquisição de itens alimentares, Mores et al (2017) dividiram os estados do país em cinco grupos. Destacaram a importância das análises demográficas e migratórias no desenvolvimento de novos hábitos alimentares e destacaram a importância do estudo pormenorizado das dinâmicas de aquisição e consumo dos estados pertencentes a nova fronteira agrícola (região denominada de Matopiba, composta pelos estados do Maranhão, Tocantins, Piauí e Bahia).…”
Section: Produtos Ultraprocessadosunclassified